Nonuniform Dependence on Initial Data of a Periodic Camassa-Holm System - Xiaohuan Wang (Abstract and Applied Analysis)
This paper is concerned with some properties of a periodic two-component Camassa-Holm system. By constructing two sequences of solutions of the two-component Camassa-Holm system, we prove that the solution map of the Cauchy problem of the two-component Camassa-Holm system is not uniformly continuous in Hs (𝕊), s>5/2.